Legal Protection of Social Security and Forms of Providing Accountability, Coaching, and Welfare for Indonesian National Athletes - Wangsa Chandra, Charlie Putra; djulaeka, Djulaeka (International Journal Labs, 2024)
The aim of this research is to analyze the legal protection provided by athletes for those who are not included in the social security program in the event of an injury and old-age pension security. National athletes have basic rights such as the right to education, health and protection from exploitation. They also have the right to receive appropriate rewards for their efforts and achievements in sports. Legal protection is necessary to ensure that these rights are respected and protected. The government has an important role in the legal protection of national athletes, including in terms of funding, coaching, accountability, training, sports facilities and sports promotion. The government also has an obligation to protect athletes from exploitation and discrimination. In order to achieve brilliant sporting achievements, strong legal protection for national athletes is very important. This provides encouragement for athletes to fully commit to their sport without having to worry about any legal issues that may arise. Thus, legal protection for national athletes is an essential aspect in advancing sports and encouraging future generations of athletes to achieve higher achievements.